The Influence of Social Media Engagement, Recommendation Accuracy, and Brand Ethical Image on Digital Brand Trust in Online Modern Retail - Sonya Sidjabat; Iwan Henri Kusnadi; Vivid Violin; Victor Lamboy Sinaga; Sagita Charolina Sihombing; Dina Agnesia Sihombing (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The research mainly aimed at exploring in-depth the determinants of digital brand trust in Indonesia's online retail fashion industry, namely, social media engagement, accuracy of recommendations, and the brand's moral image. The rationale for the study is founded on the increasing number of players in the digital retail market and trust of consumers being the primary requirement for online transactions. A quantitative explanatory technique was utilized with 200 respondents who were purposively sampled from active online shopping users. A five-point Likert scale questionnaire was used for data collection and multiple linear regression was the analysis method applied. The findings revealed that the three independent variables, as a whole, positively and significantly affected digital brand trust. On the theoretical side, this research contributes to the literature of digital marketing and consumer behavior in the context of brand trust building in the online environment. The practical implications of the research results are seen in the area of digital retail managers' strategy restructuring for winning consumers' trust through increased social media interaction, more precise recommendation systems, and ethical and transparent business practices.